Land use change and ecosystem services in mountainous watersheds: Predicting the consequences of environmental policies with cellular automata and hydrological modeling. (December 2019) - Kim, Ilkwon; Arnhold, Sebastian; Ahn, Sora; Le, Quang Bao; Kim, Seong Joon; Park, Soo Jin; Koellner, Thomas
Abstract: Integrated model systems that simulate land use and land cover change (LUCC) and associated changes of ecosystem services (ES) are increasingly important for supporting policies and management decisions. However, only few model frameworks exist that consider policy options as drivers of future LUCC and ES simultaneously. We present a modeling procedure that predicts policy-induced LUCC and ES through a combination of cellular automata (CA) and the Soil and Water Assessment Tool (SWAT). We employed this procedure to assess the efficiency of alternative policy instruments including direct payments and command-and-control regulations in mountain watersheds of South Korea. Our approach successfully captures spatial patterns of LUCC, hydrological processes, and the associated gains and losses in ES as well as potential negative externalities ("leakage" effects). Our modeling procedure provides an informative and robust basis for the development of decision support systems for mountain watersheds, where water provision and regulation are of particular concern. Highlights: We present a modeling procedure that predicts policy impacts on LUCC and ES. The procedure captures spatially explicit LUCC dynamics and supply and losses in ES. Outputs reveal highly site-specific and scale-dependent performance of policy instruments. The modeling procedure provides a robust basis for developing decision support systems.